Development of Carbon-fiber Composite Electric Cabinet of Railway Vehicles - Bo LIU; Yuyin LI; Jianling LI; Jun GUO; Zun WANG; Haitao CHENG; Chaoyi PENG (机车电传动)
Carbon-fiber composite has become the preferred material for lightweight engineering applications, because of its high specific intensity, high specific stiffness, and good structural designability. With an aluminium alloy electric cabinet as the model prototype, a carbon-fiber composite cabinet was designed, and the contrastive FEA of static strength and modal was finished, which passed the shock and vibration and protection tests. According the results of FEA and tests, the carbon-fiber composite electric cabinet could meet the operation requirements for railway vehicles with good lightweight effect, which accumulated experience for the future application of carbon-fiber composites in the electrical equipment of railway transit.